A Conundrum Concerning Creation - Haji, Ishtiyaque (Sophia, 2009)
In this paper, I expose a conundrum regarding divine creation as Leibniz conceives of such creation. What energizes the conundrum is that the concept of omnibenevolence—“consequential omnibenevolence”—that the Leibnizian argument for the view that the actual world is the best of all possible worlds presupposes, appears to sanction the conclusion that God has no practical reasons to create the actual world.